Does growth of Limosilactobacillus reuteri DSM 17938 in infant formula have an impact on its probiotic features? - Hägg, Astrid; Marklund, Carolin (SLU/Department of Molecular Sciences, 2022)
The human gut microbiota establishes at birth and forms a life-long relationship with its host. A rich diversity in the microbiota has been suggested as a key association for healthy individuals. To ensure a microbial equilibrium, clinically proven beneficial bacteria in the form of probiotics can be applied. Limosilactobacillus reuteri DSM 17938 is one of the most studied and documented probiotic strains. A prerequisite for a probiotic product today is that it contains live microorganisms, and probiotics are therefore assessed on their viability. However, whether a probiotic ought to contain solely live bacteria or a mix of dead and live bacteria including their metabolites is an ongoing discussion. Postbiotics are on the contrary non-viable by definition, instead, their efficiency is based on properties of different bacterial bioactive components and metabolites. Both probiotics and postbiotics have been applied in the production of infant formula with the aim to mimic human breast milk with its complex composition. Interaction studies of bacteria grown in infant formula are of interest as the final product can contain both live probiotics and postbiotics such as short chain fatty acids (SCFA) and membrane vesicles (MV) with reported beneficial effects. The present study intended to evaluate if fermentation of DSM 17938 in different infant formulas could affect its probiotic features. Two different infant formulas (formula A& B) were used as fermentation media and after lyophilization the bacterial tolerance to bile salts and low pH, as well as ability to adhere to mucus membranes was assessed. In addition, HPLC was performed on the supernatants to examine presence of metabolites. First of all, the bacteria both grew better and survived drying better in formula A than in formula B. Furthermore, it was shown that bacteria cultivated in formula A had a better tolerance for both gastric acid and bile than the bacteria grown in formula B. Interestingly, the HPLC results showed that only the bacteria grown in formula B had produced glycerol, whereas propionate was found in both formula A and B after fermentation. Although the reason for the different bacterial activity between the two formulas is most likely multifactorial, it can be concluded that fermenting DSM 17938 in infant formula does affect its probiotic features. Despite the fact that neither of the infant formulas in this experiment are optimized for bacterial growth, L. reuteri DSM 17938 showed a relatively good growth. The demonstrated bacterial growth in formula A and B entails that this type of fermentation media can be considered for DSM 17938 in prospective probiotic products like fermented infant formulas (FIFs). Future studies may include further investigation of the composition of infant formula A and B to untangle their potential as fermentation medium in a FIF product. In addition, this study suggests a more comprehensive definition of products such as FIFs which goes beyond the information obtained by viability.